Intersektionalität und Postkolonialität : Kritische feministische Perspektiven auf Politik und Macht - Leinius, Johanna; Mauer, Heike (Politik und Geschlecht, 2021)
This edited volume shows the added value of intersectional and postcolonial approaches for feminist research on power and domination and discusses the relationship between the two approaches. The contributors show how these innovative critical approaches enrich current debates in political science on Islamic religion, incarceration, the ethics of biomedical research, the welfare state, and ecological and student movements in the global South, among others.